Nuclear distribution of actin and myosin I depends on transcriptional activity of the cell - Kyselá, Katarína; Philimonenko, Anatoly A; Philimonenko, Vlada V; Janácek, Jirí; Kahle, Michal; Hozák, Pavel (Histochemistry and cell biology, 2005)
As previous studies suggested, nuclear myosin I (NMI) and actin have important roles in DNA transcription. In this study, we characterized the dynamics of these two proteins during transcriptional activation in phytohemagglutinin (PHA) stimulated human lymphocytes. The stimulation led to strong up-regulation of NMI both on the mRNA and protein level, while actin was relatively stably expressed. The intranuclear distribution of actin and NMI was evaluated using immunogold labeling. In nucleoli of resting cells, actin was localized predominantly to fibrillar centers (FCs), while NMI was located mainly to the dense fibrillar component (DFC). Upon stimulation, FCs remained the main site of actin localization, however, an accumulation of both actin and NMI in the DFC and in the granular component was observed. In the nucleoplasm of resting lymphocytes, both actin and NMI were localized mostly in condensed chromatin. Following stimulation, the majority of both proteins shifted towards the decondensed chromatin. In transcriptionally active cells, both actin and NMI colocalized with nucleoplasmic transcription sites. These results demonstrate that actin and NMI are compartmentalized in the nuclei where they can dynamically translocate depending on transcriptional activity of the cells.
Keywords: Microscopy, Electron, Transmission; lymfocyty; Myosin Type I; Cell Nucleolus; Transcription, Genetic; lidé; Cell Nucleus; fytohemaglutininy; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; RNA, Messenger; buněčné jádro; genetická transkripce; Reverse Transcriptase Polymerase Chain Reaction; aktiny; myosin typu I; Actins; Lymphocytes; Phytohemagglutinins; transmisní elektronová mikroskopie; buněčné jadérko; Humans